Analisis PEMANFAATAN TEKNOLOGI DALAM PENGELOLAAN ZAKAT DI ERA DIGITAL - nazila, jihan (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to analyze the optimization of digital technology in zakat management in Indonesia, identifying the benefits and challenges of its implementation. The main issue addressed is the low realization of zakat collection compared to its potential, despite digital technology's capacity to improve efficiency and transparency in zakat management. The novelty of this study lies in its comprehensive analysis of opportunities and barriers in applying technology to the zakat ecosystem in the digital era. Using a literature review method, the study examines various sources, including academic journals, zakat institution reports, and relevant articles, to gain insight into the implementation of technology in zakat management. The findings show that digital technology, such as mobile applications, blockchain, and big data, facilitates zakat collection and distribution. However, challenges remain, including data security, low digital literacy, and limited public trust in digital zakat systems. Recommendations focus on regulatory strengthening and public education to maximize the benefits of digital zakat.